(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Suicidal behavior, particularly in its chronic or recurrent forms, represents a major challenge in modern psychiatry. Individuals with personality disorders, especially borderline personality disorder (BPD), are at significantly higher risk due to emotional dysregulation, impulsivity, and persistent patterns of self-destructive behavior. Suicide attempts in this population are often recurrent, which emphasizes the need for effective relapse prevention strategies. The aim of this study is to evaluate the effectiveness of a comprehensive psychotherapeutic intervention in preventing recurrent suicidal behavior in adults with personality disorders. The study focuses on modern therapeutic approaches including dialectical behavior therapy (DBT), cognitive-behavioral therapy (CBT), psychoeducation, crisis intervention techniques, and group-based support. Based on observations of 68 patients diagnosed with BPD, two groups were formed: one received standard outpatient care, while the other completed a 12-week structured therapy program. Follow-up assessments using the Beck Scale for Suicide Ideation (BSS) and tracking of suicide attempts over a six-month period revealed a significant reduction in suicidal ideation and recurrence rates in the intervention group. These findings suggest that a multi-level psychotherapeutic model aimed at emotional regulation, stress management, and the development of adaptive coping strategies is effective in preventing recurrent suicide attempts in individuals with personality disorders.